Bare Feet and Sacred Ground: "Viṣṇu Was Here" - Nugteren, Albertina (Religions, 2018)
The meaning of a symbol is not intrinsic and should best be seen in relation to the symbolic order underlying it. In this article we explore the ritual complexities pertaining to the body's most lowly and dirty part: the feet. On entering sacred ground persons are admonished to take off their footwear. In many parts of Asia pointing one's feet in the direction of an altar, one's teacher or one's elders is considered disrespectful. Divine feet, however, are in many ways focal points of devotion. By reverently bowing down and touching the feet of a deity's statue, the believer acts out a specific type of expressive performance. The core of this article consists of a closer look at ritualized behavior in front of a particular type of divine feet: the natural footprint' (viṣṇupāda) at Gayā, in the state of Bihar, India. By studying its storied' meaning we aspire to a deepened understanding of the divine footprint' in both its embodiedness and embeddedness. Through a combination of approachestextual studies, ritual studies, ethnographywe emplace the ritual object in a setting in which regional, pan-Indian, and even cosmogonic myths are interlocked. We conclude that by an exclusive focus on a single ritual objectas encountered in a particular locationan object lesson about feet, footsteps, foot-soles, and footprints opens up a particular grammar of devotion' in terms of both absence and presence.